THE DANCE AS SOCIAL MOVEMENT: HISTORY AND EVOLUTION (Fiep Bulletin - online, 2013)
This article traces, in outline, the history and evolution of dance along History of mankind. It also stresses its social changes and functions from prehistoric times till Contemporary age, emphasizing that nowadays dance can serve not only as an artistic entertaining activity but also as a collective or personal activity for communication and physical, social, psychological welfare development.
Keywords: dance; body; movement